Intimidation or harassment among family medicine residents in Saskatchewan: a cross-sectional survey - Coleman, Andre; Reis, Olivia; Clay, Adam; Ramsden, Vivian; Kaitlyn Hughes, Kaitlyn (Canadian Medical Education Journal, 2023)
Introduction: Up to 98% of practicing family physicians, and over 75% of resident physicians in Canada experience abusive incidents. Despite the negative consequences of abusive incidents, few residents report these events to their supervisors or institution. We sought to estimate the prevalence of abusive incidents experienced or witnessed by Saskatchewan family medicine residents (FMRs) and identify their responses to these events. Methods: Anonymous survey invitations were emailed to all 110 Saskatchewan FMRs in Saskatchewan in November and December 2020. Demographic characteristics, frequency of witnessed and experienced abusive incidents, sources of incidents and residents’ responses were collected. Incidents were classified as minor, major, severe, or as racial discrimination based on a previously published classification system. Results: The response rate was 34.5% (38/110). Ninety-two percent (35/38) of residents witnessed a minor incident and 91.7% (32/36) of residents experienced a minor incident. Seventy-one percent (27/38) of residents witnessed racial discrimination while 19.4% (7/36) of residents experienced racial discrimination. Patients were the most common source of abusive incidents. Twenty-nine percent of residents reported abusive incidents to their supervisors. Most residents were aware of institutional reporting policies. Conclusions: Most Saskatchewan FMRs experienced or witnessed abusive incidents, but few were reported. This study provided the opportunity to reassess policies on abusive incidents, which should consider sources of abuse, confidence in reporting, and education.